Studying the Relationship between Talent Management and Workforce Productivity in Governmental Organizations of Bam City - Zadeh, Mehdi Jazini; Ahmadi, Yousuf (International Review of Management and Marketing, 2017)
The purpose of present research is to study the relationship between talent management (TM) and workforce productivity (WP) in governmental organizations of Bam City. The research method is descriptive-correlative and the universe includes all 3249 employees working in governmental organizations of Bam City. The sampling was done through Cochran formula and 344 employees were selected randomly as the sample size. The needed data were collected by means of Armstrong's TM questionnaire (2006) and WP questionnaire of Hersey and Goldsmith (1980). The obtained data were analyzed by LISREL software and the hypotheses were tested by structural equations. The obtained results confirmed the positive and significant relationship between TM (talent acquisition, development and retaining) and WP. Keywords: productivity, TM, talent acquisition, talent development, talent retaining JEL Classifications: C32; O13; O47